Factors Affecting the Decision Toward Home Delivery Service in Nakhon Ratchasima - ดวงกันยา, วันเฉลิม; ภู่บุบผาพันธ์, สุธาทิพย์ (RMUTI Journal Humanities and Social Sciences, 2019)
The purposes of this studying are, the first, to study the choosing food delivery behavior, the second, to study the factors priority of selecting these services, and the third, to compare the factors that affect the selecting these services in Meaung district, Nakhon Ratchsima. The sample group is the customers, used this service, which is 456 persons. This group is separated into two group that are chosen and may chose or unsure customers. The tools that is used for collecting data is the questionnaire. The collected data is analyzed by frequency, percentage and T-test. For examining, how the difference or comparing of average factors affect to the customers decision. As the result, this research showed that, the first, the more choosing food delivery behavior on Monday to Friday, there are more than 5 times the experience of using the service and most of the delivery places are residential. Channel ordering food through an application on their mobile phones and the average price of food is 100 - 500 baht. The second, the importance of the decision-making factors in using the services of the group may or may not be as high as the appearance of the food. And the importance of the decision factors of choosing the service of the group to choose the service at the highest level is the factor of delivery to meet the place specified. And the third, factors influencing the decision to choose the delivery service of the selected group may be uncertain or uncertain, significant difference at 90 % confi dence level. There are two factors, updates to the menu are up to date and there are many restaurants to choose from.